A descriptive analysis of cite units from the perspectives of content and linguistic expressions - Watanabe, Koichiro (2022)
Background: While the use of citations for assessing research impact is well-studied, there is little work that investigates the content introduced into the citing documents through citations and the linguistic expressions used to represent the cited content Objectives: This study analysed the types of content introduced into citing documents using the citations (cited content) and units of linguistic expressions used to represent the cited content. Methods. We classified the expressions representing the cited content according to the unit of linguistic expressions (terms and clauses) and classified the cited content into conceptual categories. We adopted different frameworks for the classification of cited content represented by terms and clauses. The categories for terms were domain specific and the categories for clauses took into account subjectivity and generality. We also described the detailed categories of cited content with examples and provided seven types of cited content for clauses. Results: We found that among the expressions representing cited content, terms constituted about 40% and clauses constituted about 60%. The majority of the cite terms were domain specific; and 35% of the cite terms referred to unique concepts. Of the cite clauses, 50% were objective and term-specific, 40% were objective and general, and 10% were subjective. Contributions: This research provided a description of cite units and elaborated on the categories for cited content. The results showed basic types of cited content and clarified the distribution of cite units.